Kecerdasan Spiritual Dengan Terapi Ibadah - Rusyaida, Rusyaida (Alhurriyah, 2013)
Ibadah (act of devotion) has the function to calm down the restless that come out from the guilty feeling. It gives the peacefulness to the religion follower. Besides, it also teaches the sublime values such as patience, endurance, discipline, empathy, social solidarity and passion restraint. These values are the important indicator in psychological health.